Mangrove clearing impacts on macrofaunal assemblages and benthic food webs in a tropical estuary. (January 2018) - Bernardino, Angelo Fraga; Gomes, Luiz Eduardo de Oliveira; Hadlich, Heliatrice Louise; Andrades, Ryan; Correa, Lucas Barreto
Abstract: Despite over 21, 000 ha of mangrove forests being removed per year in Brazil, ecological changes following mangrove deforestation have been overlooked. Here we evaluated changes in benthic macrofaunal assemblages and food-webs at a mangrove removal and natural sites in a tropical estuary in Eastern Brazil. The impacted site had coarser sediment particle sizes suggesting significant changes in sedimentation processes after forest clearing. Spatial differences in macrofaunal abundance, biomass and diversity were not directly associated with the removal of mangrove forests, supporting recolonization of impacted areas by estuarine fauna. However, benthic assemblage composition, infaunal δ 13 C signatures and food-web diversity markedly differed at the impacted site being strongly related to sedimentary changes. The loss of infaunal trophic diversity that followed mangrove removal suggests that large-scale forest clearing may impact estuarine food webs, with potential consequences to nearby coastal ecosystems given the high clearing rate of mangrove forests in Brazil. Graphical abstract: Highlights: Mangrove clearing increased sediment grain size. Benthic assemblages changed in the cleared areas and on nearby mudflats. Benthic food-webs were impacted by lower trophic diversity. Mangrove clearing impacts on coastal trophic dynamics need to be investigated.